Implementation of a Streamlined Care Pathway to Reduce Cost and Length of Stay for Patients Undergoing Transsphenoidal Pituitary Surgery. (16th November 2020) - Miranda, Stephen; Blue, Rachel; Dimentberg, Ryan; Thurlow, Jennifer; Lebold, David; Hudgins, Justine; Ebesutani, Darren; Lerner, David; Parasher, Arjun; Glicksman, Jordan; Adappa, Nithin; Grady, Michael S
Abstract: INTRODUCTION: Endoscopic transsphenoidal (TSA) pituitary surgery is associated with significant cost variability. Given the growing focus on value-based care, our department developed and implemented a streamlined care pathway for TSA patients. Instead of standard admission to the intensive care unit, select patients are recovered in the post-anesthesia care unit (PACU) and transferred to a step-down unit for intermediate neurologic care (INCU), with specialized nurses and clinicians trained to recognize and manage known complications of TSA pituitary surgery, including cerebrospinal fluid leak and diabetes insipidus. METHODS: We evaluated all TSA pituitary surgeries performed at one academic medical center from July 1, 2017, to March 30, 2020. The electronic medical record was reviewed for patient factors, tumor characteristics, and cost variables during each hospital stay. The INCU pathway was implemented on July 1, 2018, and all pathway patients were noted. Univariate linear regression was performed using Stata software. RESULTS: The analysis included 187 total patients, 79 of whom were on the INCU pathway after implementation. Mean age was 53.5 years, and the majority of patients were male (66%), privately insured (62%), and Caucasian (66%). Mean total cost of admission was 27276 and mean length of stay was 3.97 days. The use of the INCU pathway was associated with a reduction in total cost of 6035.63 ( P < . 001, 95% CI: 3308.26-8762.99) and a reduction in length of stay of 1.17 days ( P = . 012, 95% CI: 0.255-2.08). In-hospital costs were reduced across all domains, including: 1866.19 in variable direct labor costs ( P < . 001, 95% CI: 1045.50-2686.88), 1137.52 in variable direct supply costs ( P < . 001, 95% CI: 682.10-1592.93), 1099.53 in fixed direct costs ( P = . 001, 95% CI: 439.71-1759.35), and 1932.39 in indirect costs ( P < . 001, 95% CI: 1019.22-2845.56). CONCLUSION: Use of a streamlined care pathway following TSA pituitary surgery can be a successful approach to reducing in-hospital costs and length of stay for patients without surgical or medical contraindications to early discharge.